Determining the minimally important difference in quadriceps strength in individuals with COPD using a fixed dynamometer - Vaidya T; Beaumont M; de Bisschop C; Bazerque L; Le Blanc C; Vincent A; Ouksel H; Chambellan A (International Journal of COPD, 2018)
Trija Vaidya,1,2 Marc Beaumont,3,4 Claire de Bisschop,1 Lucie Bazerque,5 Camille Le Blanc,6 Anne Vincent,7 Hakima Ouksel,8 Arnaud Chambellan2,9 1Laboratory MOVE (EA6314), Faculty of Sport Sciences, University of Poitiers, Poitiers, France; 2Laboratory “Movement, Interactions, Performance” (EA4334), Faculty of Sport Sciences, University of Nantes, Nantes, France; 3Pulmonary Rehabilitation unit, Morlaix Hospital Centre, Morlaix, France; 4EA3878 (G.E.T.B.O), CHU Brest, Brest, France; 5Institute of Physical Education and Sports Sciences (IFEPSA), Université Catholique de l’Ouest (UCO), Angers, France; 6Physical Medicine and Rehabilitation Department, University Hospital of Nantes, Nantes, France; 7Respiratory Rehabilitation Service, la Tourmaline, UGECAM, Nantes, France; 8Dept of Pulmonary Medicine, Angers University Hospital, Angers, France; 9l’institut du Thorax, University Hospital of Nantes, Nantes, France Background: Measurement of quadriceps muscular force is recommended in individuals with COPD, notably during a pulmonary rehabilitation program (PRP). However, the tools used to measure quadriceps maximal voluntary contraction (QMVC) and the clinical relevance of the results, as well as their interpretation for a given patient, remain a matter of debate. The objective of this study was to estimate the minimally important difference (MID) of QMVC using a fixed dynamometer in individuals with COPD undergoing a PRP. Methods: Individuals with COPD undergoing a PRP were included in this study. QMVC was measured using a dynamometer (MicroFET2) fixed on a rigid support according to a standardized methodology. Exercise capacity was measured by 6-minute walk distance (6MWD) and evaluation of quality of life with St George’s respiratory questionnaire (SGRQ) and Hospital Anxiety and Depression Scale (HADS) total scores. All measures were obtained at baseline and the end of the PRP. The MID was calculated using distribution-based methods. Results: A total of 157 individuals with COPD (age 62.9±9.0 years, forced expiratory volume in 1 second 47.3%±18.6% predicted) were included in this study. At the end of the PRP, the patients had improved their quadriceps force significantly by 8.9±15.6 Nm (P<0.001), as well as 6MWD by 42±50 m (P<0.001), SGRQ total score by -9±17 (P<0.001) and HADS total score by -3±6 (P<0.001). MID estimation using distribution-based analysis was 7.5 Nm by empirical rule effect size and 7.8 Nm by Cohen’s effect size. Conclusion: Measurement of QMVC using a fixed dynamometer is a simple and valuable tool capable of assessing improvement in quadriceps muscle force after a PRP. We suggest an MID of 7.5 Nm to identify beneficial changes after a PRP intervention. Keywords: COPD, QMVC, muscular dysfunction, dynamometer, pulmonary rehabilitation